Enhancing regional process safety management. (July 2021) - Khan, Aadil; Sattari, Fereshteh; Lefsrud, Lianne; Tufail, Modusser
Abstract: As industrial operations expand, major incidents continue to affect people, damage facilities, and impact the environment. In the last 20 years, about 50% of these incidents occurred in facilities that had implemented some form of Process Safety Management (PSM) and 50% came about in smaller facilities that did not include such planning (Demichela et al., 2004). The objective of this article is to use PSM principles to create practical recommendations at the regional level, to complement those previously developed for singular facilities. This article compares Strathcona County Emergency Service (SCES) in Alberta with Technical Standards & Safety Authority (TSSA) in Ontario, with respect to safety, facility licensing, permit requirements, risk assessment procedures and land use planning aspects to determine PSM enhancements for SCES. Furthermore, for a better overview, two supplemental provincial organisations in Alberta, namely Alberta Boiler Safety Association (ABSA) and Safety Codes Council (SCC), were also considered. We proposed that SCES could develop more detailed facility-specific licensing procedures, auditing, and inspection. SCES could also provide details of accredited organisations that carry out inspections and audits on their behalf. When reviewing the quantitative risk assessment processes for SCES and TSSA, we recommend that SCES should update their probability data sources used in their cumulative risk assessment study. Based on the authors' experience and gathered data, the use of additional facility practices such as safety management system, internal audits, and checklists can enhance incident prevention. Highlights: Half of process safety management (PSM) incidents have occurred in smaller facilities that have not adopted PSM tools. Thus, our objective is to create regional recommendations to enhance PSM for single facilities. We review regulations for Strathcona County in Alberta and Technical Standards & Safety Authority (TSSA) in Ontario. Then, we compare their facility licensing, permit requirements, risk assessment procedures, and land use planning. We conclude with recommendations to enhance regional safety management systems, internal audits, and checklists.